Simulating the pre‐ and de‐emphasis of drive voltages of silicon‐based micro‐ring ring‐modulators. Issue 5 (1st March 2017) - Tenenbaum, S.
Abstract : Integrated modulators are being intensely investigated and became potential candidates for the fundamental building blocks of next generation silicon‐based front‐end transceivers. Although suitable optical performance has been demonstrated in several works, theoretical models for the appropriate driving conditions of the micro‐ring modulators are rarely explored. The carrier concentration fundamentally determines the refraction index of the pn junction of the modulator and to accelerate charge injection/extraction a pre‐ and de‐emphasised driving voltage technique has been widely and successfully applied. Here we present a mathematical model where shooting amplitude and duration are considered with an optimised power consumption analysis. The model can be applied for both NRZ and RZ modulation formats.